Kapasitas Kelembagaan Pemerintah Desa dalam Pengelolaan Badan Usaha Milik Desa di Kabupaten Sumedang - Idah Wahidah; Dian Herdiana (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
One of the goals of national development is the development that starts from the village, where one of the efforts is to build village-owned enterprises. Based on this understanding, this article is intended to analyze the management of Village-Owned Enterprises with a research question, namely, how is the institutional capacity of the village government in managing village-owned enterprises in Sumedang Regency. The research method used is a descriptive research method with a qualitative approach. The data come from primary research and secondary data from various relevant references. The study results revealed that the village government's institutional capacity in managing village-owned enterprises is already good; this is indicated by most village-owned enterprises in the Sumedang district, which are already developing and advanced. Good institutional capacity is shown by the individual attitude of administrators who can adequately manage village-owned enterprises and are supported by management that is in line with existing regulations.